Evidence for bipolar explosions in Type IIP supernovae - Nagao, T.; Maeda, K.; Mattila, S.; Kuncarayakti, H.; Kawabata, M.; Taguchi, K.; Nakaoka, T.; Cikota, A.; Bulla, M.; Vasylyev, S. S.; Gutiérrez, C. P.; Yamanaka, M.; et al. (EDP Sciences, 2025)
Aims. Recent observations of core-collapse supernovae (SNe) suggest aspherical explosions. Globally, aspherical structures in SN explosions are thought to encode information regarding the underlying explosion mechanism. However, the exact explosion geometries from the inner cores to the outer envelopes are poorly understood.
Methods. Here, we present photometric, spectroscopic, and polarimetric observations of the Type IIP SN 2021yja and discuss its explosion geometry in comparison to those of other Type IIP SNe that show large-scale aspherical structures in their hydrogen envelopes (SNe 2012aw, 2013ej and 2017gmr).
Results. During the plateau phase, SNe 2012aw and 2021yja exhibit high continuum polarization characterized by two components with perpendicular polarization angles. This behavior can be interpreted as being due to a bipolar explosion, where the SN ejecta is composed of a polar (energetic) component and an equatorial (bulk) component. In such a bipolar explosion, an aspherical axis created by the polar ejecta would dominate at early phases, while the perpendicular axis along the equatorial ejecta would emerge at late phases after the photosphere in the polar ejecta has receded. Our interpretation of the explosions in SNe 2012aw and 2021yja as bipolar is also supported by other observational properties, including the time evolution of the line velocities and the line shapes in the nebular spectra. The polarization of other Type IIP SNe that show large-scale aspherical structures in the hydrogen envelope (SNe 2013ej and 2017gmr) is also consistent with the bipolar-explosion scenario, although this is not conclusive.